Cathepsin S regulates antitumor immunity through autophagic degradation of PD-L1 in colorectal cancer cells - Sina Taheri Baghmisheh; Chung-Hsing Chen; Yu-Min Yeh; Peng-Chan Lin; Po-Chuan Chen; Ren-Hao Chan; Jui-Wen Kang; Chung-Ta Lee; Hui-Ju Tsai; Yu-Chen Fang; Chun Hei Antonio Cheung; Kwang-Yu Chang; et al. (Cancer Immunology, Immunotherapy)
Abstract Colorectal cancer (CRC) is a major contributor to cancer-related mortality worldwide, highlighting the need to overcome its immunosuppressive tumor microenvironment. Cathepsin S (CTSS), a cysteine protease essential for MHC class II antigen presentation, has an unclear role in CRC immunity. This study investigated the impact of CTSS on PD-L1 expression and T-cell function in CRC. CTSS expression was analyzed in CRC tumor tissues and CTSS-deficient cell lines using immunohistochemistry, Western blotting, and flow cytometry. T-cell responses were assessed through granzyme B and IL-2 secretion assays, migration analysis, and gene set variation analysis (GSVA) of public datasets. Autophagy activity was evaluated via immunofluorescence, Western blotting, and lysosome isolation assays. An orthotopic CRC mouse model was used to study CTSS function in vivo. Key findings revealed that elevated CTSS expression correlated with higher PD-L1 levels in CRC tissues. CTSS suppression in CRC cells reduced PD-L1 expression while enhancing T-cell cytotoxicity and migration. GSVA further revealed an inverse correlation between CTSS expression and cytotoxic T-cell activity, alongside a strong association with autophagy-related pathways. Mechanistically, CTSS suppression in CRC cells promoted PD-L1 degradation by enhancing autophagic flux. In vivo, CTSS suppression inhibited tumor growth and enhanced CD8⁺ T-cell infiltration and activity. Anti-CD8 antibody treatment promoted tumor growth more significantly in CTSS-proficient CRC cells compared to CTSS-deficient cells. These findings demonstrate that CTSS regulates PD-L1 expression and T-cell cytotoxicity via autophagy-mediated pathways in CRC cells. Given ongoing development of CTSS inhibitors and autophagy modulators, targeting CTSS may offer a promising strategy to improve CRC immunotherapy.